Organizational strengthening as a village-owned enterprise capacity development effort in central Mamuju regency - Dzulkifli, Dzulkifli; Ahmad, Badu; Abdullah, Muh Tang; Ibrahim, Muhammad Akmal; Pauzi, Rizal (Edelweiss Applied Science and Technology, 2025)
This research examines organizational strengthening strategies to develop the capacity of Village-Owned Enterprises in Central Mamuju Regency, Indonesia. The study focuses on four key organizational dimensions: incentive systems, personnel utilization, communication, and managerial structure. Using a descriptive qualitative approach with a case study design, data were collected through in-depth interviews with 16 key informants, focus group discussions with stakeholders, direct observation of Village-Owned Enterprise management practices, and document analysis. The research results reveal significant challenges in organizational management, including inadequate implementation of professional management principles, suboptimal organizational structures, and limited transparency in decision-making processes. The study also identifies challenges in organizational culture, particularly the dominant "government project" paradigm rather than an entrepreneurial orientation, as well as budget resource limitations, with restricted capital allocation and ineffective financial management systems. Based on these findings, the research proposes a comprehensive organizational strengthening model that integrates incentive system reforms through a hybrid model combining fixed salaries with performance-based profit sharing; enhanced personnel utilization through competency-based selection and continuous capacity development; strengthened effective communication with stakeholders; and restructuring of managerial systems in accordance with current regulations. This model aims to transform Village-Owned Enterprises into independent, professional, and sustainable economic institutions that effectively contribute to rural development in Central Mamuju Regency.